2009
DOI: 10.1007/s10620-009-0762-z
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress, Somatization, and Defense Mechanisms Associated with Quality of Life in Inflammatory Bowel Disease Patients

Abstract: Somatization and reaction-formation are independent correlates of disease-specific HRQOL in IBD patients, and this could be relevant to psychological interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 43 publications
(67 reference statements)
1
16
0
1
Order By: Relevance
“…We and others have shown that anxiety, depression and the physical aspects of disease severity or activity are associated independently with HRQOL in inflammatory bowel disease [26][27][28] and that, in these patients, somatization (i.e., the number of bodily symptoms) is associated with HRQOL independent of anxiety and depression [29]. We examine here whether the same is true in patients with several well-established physical diseases.…”
Section: Introductionmentioning
confidence: 84%
“…We and others have shown that anxiety, depression and the physical aspects of disease severity or activity are associated independently with HRQOL in inflammatory bowel disease [26][27][28] and that, in these patients, somatization (i.e., the number of bodily symptoms) is associated with HRQOL independent of anxiety and depression [29]. We examine here whether the same is true in patients with several well-established physical diseases.…”
Section: Introductionmentioning
confidence: 84%
“…In another study, Carvalho et al [21] evaluated the association between defense mechanisms and HRQoL in hemodialysis patients (HD), and found splitting, projection, reaction formation and denial to be associated with impaired HRQoL in these patients. Additionally, in inflammatory bowel disease patients, Hyphantis et al [20] showed an association between somatization and quality of life, independent of depression and anxiety.…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…Ego defense mechanisms are defined as "automatic psychological processes that protect the individual against anxiety mediating the individual's reactions to emotional conflicts and to internal or external stressors" [19]. In some organic diseases, such as inflammatory bowel disease, rheumatoid arthritis and hemodialysis, associations between ego defense mechanisms and health-related quality of life have been reported [20,21,22]. However; until now, the roles of deep psychological constructs, such as ego defense mechanisms, in neuropathic pain have not been studied and established.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Among individuals with IBD, HRQoL is influenced by the longitudinal profile of disease activity, 11 female gender, lower education, 12 clinical symptoms, and illness representations, 13 as well as by psychological distress, somatization, social support, and personality factors, including coping capacities. 10,14,15 Frequently, when facing the burden, stress, and limitations imposed by a chronic illness, patients find relief and control in a process referred to as religious coping. 16 Religious coping is linked to five key objectives: search for meaning, control, spiritual comfort, closeness to God and other society members, and change in life.…”
Section: Introductionmentioning
confidence: 99%